Effect of fine coke particles on rheological properties of the binder matrix of carbon anodes in aluminium production process. (12th May 2021) - Mollaabbasi, Roozbeh; Hansen, Lene Jensberg; Grande, Tor; Taghavi, Seyed Mohammad; Alamdari, Houshang
Abstract: Aluminium production through the Hall‐Héroult process relies on an extensive use of carbon anodes, which are originally made of coal tar pitch and fine and coarse carbon particles. During the forming process of green anodes, the mixture of the fine particles and the coal‐tar pitch (i.e., the binder matrix) moves between the coarse particles and produces a uniform agglomerated paste. The efficiency of the forming process directly affects the final quality of the baked anode and consequently the efficiency of the Hall‐Héroult process. The rheological properties of the binder matrix play a crucial role in the forming process. In this study, rotation and oscillation tests are used to study the effects of the fine particle concentration and temperature on the viscoelastic properties of the binder matrix. The rotation tests demonstrate that the binder matrix is a shear‐thinning material and that the viscosity is reduced by increasing the shear rate and temperature while it is increased by increasing the concentration of the fine particles. Moreover, the proposed model can predict the viscosity of the binder matrix precisely. The oscillation tests confirm that the elastic and viscous properties are reinforced by increasing the concentration of the fine particles and they are reduced by increasing the angular frequency and temperature. The three‐element Maxwell model is shown to predict the elastic and viscous moduli of the binder matrix. Finally, in a case study and based on the rheological results, the permeation velocity of the binder matrix between the coarse particles is calculated.